Affect and Incident Participation Restriction in Adults With Knee Osteoarthritis. Issue 4 (18th February 2018) - Vaughan, Molly W.; LaValley, Michael P.; Felson, David T.; Orsmond, Gael I.; Niu, Jingbo; Lewis, Cora E.; Segal, Neil A.; Nevitt, Michael C.; Keysor, Julie J.
Abstract : Objective: Participation restriction, common among people with knee osteoarthritis (OA), may be influenced by affect. We examined the risk of incident participation restriction over 84 months conferred by positive and negative affect among people with knee OA. Methods: Participants were from the Multicenter Osteoarthritis Study and had or were at high risk of knee OA. Participation restriction was measured using the Instrumental Role Limitation subscale of the Late‐Life Disability Index, and affect was measured using the positive affect and depressed mood subscales of the Center for Epidemiologic Studies Depression Scale. Robust Poisson regression was used to calculate the risk of incident participation restriction over 84 months conferred by combinations of low and high positive and negative affect, adjusting for covariates. Results: Of 1, 810 baseline participants (mean age 62.1 years, 56% female), 470 (26%) had incident participation restriction over 84 months. Participants with low positive affect had 20% greater risk of incident participation restriction than those with high positive affect; participants with high negative affect had 50% greater risk of incident participation restriction compared to those with low negative affect. Participants with both low positive and high negative affect had 80% greater risk of incident participation restriction compared to other combinations of positive and negative affect. Conclusion: Low positive and high negative affect, both alone and in combination, increase the risk of participation restriction among adults with knee OA. Efforts aimed at preventing participation restriction in this population should consider these mood states.